BUILDING A BRIDGE BETWEEN SUSTAINABILITY AND FINANCIAL PERFORMANCE: AN ANALYSIS OF SUSTAINABILITY REPORTS IN ASRRAT COMPANIES - Kinanthi Putri Ardiami; Azmi Mufidu Prahmi; Reny Lia Riantika (Global Financial Accounting Journal, 2025)
Purpose - This study examines the impact of sustainability reports on financial performance by analyzing the economic, environmental, and social aspects disclosed in sustainability reports of companies participating in the Asia Sustainability Reporting Rating (ASRRAT) from 2021 to 2023. Research Method - The study employs a purposive sampling method, selecting 30 companies with a total of 90 firm-year observations. Panel data regression analysis is applied to assess the relationships between sustainability disclosure and financial performance. Findings - The results indicate that the economic and social aspects of sustainability reports have a significant positive effect on financial performance. In contrast, the environmental aspect exerts a significant negative influence on financial performance. These findings suggest that while sustainability reporting can enhance corporate financial outcomes, certain environmental disclosures may impose additional costs that negatively impact profitability. Implication - The study provides insights for corporate managers, investors, and policymakers regarding the strategic role of sustainability reporting. Companies should emphasize economic and social sustainability disclosures to improve financial performance while managing environmental responsibilities effectively. Additionally, regulators may need to refine sustainability disclosure frameworks to ensure that environmental initiatives support both corporate and societal value creation. Keywords: Sustainability Report, Sustainability Report, Financial Performance